Nonlinear responses for chromosome and gene level effects induced by vinyl acetate monomer and its metabolite, acetaldehyde in TK6 cells. (28th August 2013) - Budinsky, Robert; Gollapudi, Bhaskar; Albertini, Richard J.; Valentine, Rudolph; Stavanja, Mari; Teeguarden, Justin; Fensterheim, Robert; Rick, David; Lardie, Thomas; McFadden, Lisa; Green, Amanda; Recio, Leslie
Abstract : Vinyl acetate monomer (VAM) produced rat nasal tumors at concentrations in the hundreds of parts per million. However, VAM is weakly genotoxic in vitro and shows no genotoxicity in vivo. A European Union Risk Assessment concluded that VAM's hydrolysis to acetaldehyde (AA), via carboxylesterase, is a critical key event in VAM's carcinogenic potential. In the following study, we observed increases in micronuclei (MN) and thymidine kinase ( Tk ) mutants that were dependent on the ability of TK6 cell culture conditions to rapidly hydrolyze VAM to AA. Heat‐inactivated horse serum demonstrated a high capacity to hydrolyze VAM to AA; this activity was highly correlated with a concomitant increase in MN. In contrast, heat‐inactivated fetal bovine serum (FBS) did not hydrolyze VAM and no increase in MN was observed. AA's ability to induce MN was not impacted by either serum since it directly forms Schiff bases with DNA and proteins. Increased mutant frequency at the Tk locus was similarly mitigated when AA formation was not sufficiently rapid, such as incubating VAM in the presence of FBS for 4 hr. Interestingly, neither VAM nor AA induced mutations at the HPRT locus. Finally, cytotoxicity paralleled genotoxicity demonstrating that a small degree of cytotoxicity occurred prior to increases in MN. These results established 0.25 mM as a consistent concentration where genotoxicity first occurred for both VAM and AA provided VAM is hydrolyzed to AA. This information further informs significant key events related to the mode of action of VAM‐induced nasal mucosal tumors in rats. Environ. Mol. Mutagen. 54:755–768, 2013. © 2013 Wiley Periodicals, Inc.